PROTEINS-REGULATORS OF IRON METABOLISM IN THE DIFFERENTIAL DIAGNOSIS OF IRON-DEFICIENCY ANEMIA - Суржикова, Галина Северьевна; Клочкова-Абельянц, Сатеник Аршавиловна (Medicine in Kuzbass, 2022)
Objective. Studies were conducted in 396 women aged 16 to 60 years. 79 of them were practically healthy and made up the control group, 317 had anemic syndrome, of which 103 women suffered from iron deficiency anemia (IDA), 214 – anemia of chronic disease (ACD). Of 214 women with ACD, 121 women were diagnosed with anemia that developed on the background of rheumatoid arthritis (RA), 93 women had anemia of chronic diseases with bacterial infections (chronic tonsillitis, bacterial endocarditis, chronic pyelonephritis).The aim of the study is to study the significance of regulatory proteins involved in iron metabolism in the differential diagnosis of iron deficiency anemia and anemia of chronic diseases.Methods. The research methods included the assessment of indicators of the peripheral link of erythron, iron metabolism, the level of soluble transferrin receptors and hepcidin. The assessment of iron stores was carried out according to the level of serum ferritin by enzyme immunoassay using test systems from Orgentec diagnostika. Hepcidin-25 in blood serum was determined by ELISA using test systems from Peninsula Laboratories, LLC.Results. A significant increase in the level of soluble transferrin receptors was revealed in IDA, while in patients with ACD this indicator did not differ from that in healthy people and was significantly lower compared to the group of patients with IDA. The content of hepcidin-25 in patients with IDA was reduced, while in patients with ACD the level of hepcidin-25 was significantly higher compared to that in healthy individuals and those with IDA.Conclusions. In the differential diagnosis of IDA and ACD, in addition to standard methods for assessing iron metabolism (serum iron, TIBC, LVCC, CNT, ferritin), studies of new proteins regulating iron metabolism have appeared, the use of which is significant in clinical practice.
Keywords: iron deficiency anemia; anemia of chronic diseases; hepcidin; ferritin; soluble transferrin receptors